Analisis Etika Pasar dalam Ekonomi Syariah terhadap Perilaku Pelaku Usaha - Lukman Lukman; Ulil Albab; Heri Sutopo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the implementation of market ethics from the perspective of Islamic economics on the behavior of business actors at Mandiri Jaya Jatimulyo Market, South Lampung Regency. Islamic market ethics are viewed as a moral instrument that guides economic activities to operate fairly, honestly, and oriented toward public welfare. This research employs a qualitative approach with a descriptive-analytical design. Data were collected through in-depth interviews, observations, and documentation involving business actors actively engaged in daily market transactions. The findings reveal that Islamic market ethical values, such as honesty, transparency, and moral responsibility, have been applied in trading practices; however, their implementation remains partial and largely dependent on individual moral awareness. Religiosity, economic pressure, the social environment of the market, and the level of Islamic economic literacy are identified as key factors influencing ethical behavior. This study concludes that strengthening Islamic market ethics in traditional markets requires a comprehensive approach involving continuous education, the development of an ethical market culture, and institutional support to ensure sustainable internalization of Islamic values.